2017
DOI: 10.1074/jbc.m117.797878
|View full text |Cite
|
Sign up to set email alerts
|

Hu antigen R (HuR) multimerization contributes to glioma disease progression

Abstract: Among primary brain cancers, gliomas are the most deadly and most refractory to current treatment modalities. Previous reports overwhelmingly support the role of the RNA-binding protein Hu antigen R (HuR) as a positive regulator of glioma disease progression. HuR expression is consistently elevated in tumor tissues, and a cytoplasmic localization appears essential for HuR-dependent oncogenic transformation. Here, we report HuR aggregation (multimerization) in glioma and the analysis of this tumor-specific HuR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 51 publications
3
54
1
Order By: Relevance
“…Previous studies showed that HuR promotes proliferation in cancer cells (20,38), including wild-type gliomas (39,40). Here, we investigated the effect of HuR expression on cell proliferation in cancer cells that harbor a natural heterozygous IDH1 mutation.…”
Section: Hur Promotes Cell Proliferation and Invasion In Mutidh1 Canmentioning
confidence: 97%
“…Previous studies showed that HuR promotes proliferation in cancer cells (20,38), including wild-type gliomas (39,40). Here, we investigated the effect of HuR expression on cell proliferation in cancer cells that harbor a natural heterozygous IDH1 mutation.…”
Section: Hur Promotes Cell Proliferation and Invasion In Mutidh1 Canmentioning
confidence: 97%
“…Previously, we reported on the vital role of HuR in GB where it is highly upregulated in tumor cells and promotes tumor progression in vivo (Filippova et al, ; Filippova et al, ; Nabors et al, ; Nabors, Gillespie, Harkins, & King, ). Blocking HuR either by chemical inhibition or shRNA‐mediated silencing can produce a potent anti‐glioma effect (Filippova et al, ; Filippova et al, ; Wang, Hjelmeland, Nabors, & King, ). In the current study, we hypothesized that HuR expression in TAMs promotes tumor progression through its role in modulating the expression of key cytokines and chemokines.…”
Section: Introductionmentioning
confidence: 97%
“…HuR can also bind to the 5 0 UTR, often at or near internal ribosome entry sites, and either inhibits or augments translation (Galban et al, 2008;Kullmann, Gopfert, Siewe, & Hengst, 2002;Meng et al, 2005). Previously, we reported on the vital role of HuR in GB where it is highly upregulated in tumor cells and promotes tumor progression in vivo (Filippova et al, 2011;Filippova et al, 2017;Nabors et al, 2003;Nabors, Gillespie, Harkins, & King, 2001). Blocking HuR either by chemical inhibition or shRNA-mediated silencing can produce a potent anti-glioma effect (Filippova et al, 2011;Filippova et al, 2017;Wang, Hjelmeland, Nabors, & King, 2019).…”
mentioning
confidence: 98%
“…DHTS showed effects similar to MS-444 in glioma, by inhibiting HuR multimerisation and decreasing cellular HuR protein level. Importantly, DHTS showed dose-dependent cytotoxicity towards glioma cells [140]. Based on the structure of DHTS, a series of tanshinone mimics were synthesised.…”
Section: Other Hur/are-rna Disruptors and Therapeutic Effectsmentioning
confidence: 99%